2011
DOI: 10.1159/000321799
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Magnifying Narrow-Band Imaging Endoscopy in the Helicobacter pylori-Related Chronic Gastritis

Abstract: Combining the narrow-band imaging (NBI) system and magnifying endoscopy allows simple and clear visualization of microscopic structures of the superficial mucosa and its capillary patterns, which may be useful for precise endoscopic diagnosis in the gastrointestinal tract, being more closely to histopathological diagnosis. In the non-neoplastic gastric mucosa, there have been reports showing a potential usefulness of magnifying NBI for the diagnosis of Helicobacter pylori infection, degree of histological gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…The another limitation of NBI system is the presence of a thick keratin layer covering underlying mucosa where NBI view could not detect microvascular changes interfered by the keratin layer 11. Thus the diagnostic accuracy of NBI may be affected by the learning curve associated with this new technique, and extra time is needed to acquire the procedure 9–14, 31, 32. A second limitation was our use of a gastrointestinal endoscope instead of a flexible fiberoptic laryngoscope.…”
Section: Discussionmentioning
confidence: 99%
“…The another limitation of NBI system is the presence of a thick keratin layer covering underlying mucosa where NBI view could not detect microvascular changes interfered by the keratin layer 11. Thus the diagnostic accuracy of NBI may be affected by the learning curve associated with this new technique, and extra time is needed to acquire the procedure 9–14, 31, 32. A second limitation was our use of a gastrointestinal endoscope instead of a flexible fiberoptic laryngoscope.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advance of image-enhanced endoscopy, NBI, blue laser imaging, and linked color imaging has improved the accuracy and reproducibility of endoscopic diagnosis of H. pylori-infected gastritis, CAG, and IM as well as premalignant lesions or early gastric cancer [18,19]. High-resolution endoscopes with magnification-NBI are highly efficient in detecting premalignant lesions or early gastric cancer [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Almost all these studies used magnifying NBI endoscopes, and the results revealed a high sensitivity and specificity for diagnosing H. pylori infection (29)(30)(31)(32). First, Alaboudy et al (12) defined four characteristic views of H. pylori infection by using a non-magnifying NBI endoscope and revealed an association between histopathological severity and endoscopic views (Figures 1-4).…”
Section: Discussionmentioning
confidence: 99%